Faktor Ibu Yang Mempengaruhi Pertumbuhan Janin Terhambat - Suryanti Sudirman; Budi Wicaksono; Siti Pariani (Indonesian Journal of Health, 2020)
Intrauterine growth retardation is one of the cause of perinatal and child mortality. Although the incidence varies from 3-10 persent because of differences in definition and standard curves in use,more important is the perinatal mortality rate with IUGR babies approximately 7-8 times higher than normal babies and more or less turned out to be 26% or more events stillbirth associated with IUGR. The research method used descriptive research to describes and illustrates the maternal factors that affect of IUGR. Sample used is all of the mother is experienced in the diagnosis of IUGR in Dr.Soetomo Hospital. The instrument used was a data collection sheet, source data from medical records, data analysis using SPSS program by looking at the frequency distribution and the relationship of each factor with the chi-square test. The results of the 39 respondents who gave birth with IUGR of 21.8% by weight of the baby is less than 1500 and 64.1% a month is not enough. Gained an average weight of babies was 1696 g and the average age of mothers who gave birth with IUGR was 31 years old. From the test results obtained statistical history of the disease and the levels of HB's mother had a powerful effect with p <0.05. This means that there is a relationship in between IUGR with a history of maternal illness and hemoglobin levels. The conclusion of this study is that maternal factors influence the occurrence of growth retardation is a history of the disease, hemoglobin levels, and hematocrit levels